Use of Electricity to Sedate Lake Trout for Intracoelomic Implantation of Electronic Transmitters. (4th July 2017) - Faust, Matthew D.; Vandergoot, Christopher S.; Hostnik, Eric T.; Binder, Thomas R.; Mida Hinderer, Julia L.; Ives, Jessica T.; Krueger, Charles C.
Abstract: Use of telemetry data to inform fisheries conservation and management is becoming increasingly common; as such, fish typically must be sedated before surgical implantation of transmitters into the coelom. Given that no widely available, immediate-release chemical sedative currently exists in North America, we investigated the feasibility of using electricity to sedate Lake Trout Salvelinus namaycush long enough for an experienced surgeon to implant an electronic transmitter (i.e., 180 s). Specifically, our study objectives were to determine (1) whether some combination of electrical waveform characteristics (i.e., duty cycle, frequency, voltage, and pulse type) could sedate Lake Trout for at least 180 s; and (2) whether Lake Trout that were sequentially exposed to continuous DC and pulsed DC had greater rates of spinal injury and short-term mortality than control fish. A Portable Electrosedation System unit was used to sedate hatchery and wild Lake Trout. Dual-frequency pulsed-DC and two-stage approaches successfully sedated Lake Trout and had similar induction and recovery times. Lake Trout sedated using the two-stage approach did not have survival rates or spinal abnormalities that were significantly different from those of control fish. We concluded that electricity was a viable alternative to chemical sedatives for sedating Lake Trout before surgical implantation of an electronic transmitter, but we suggest that Lake Trout and other closely related species (e.g., Arctic Char Salvelinus alpinus ) may require morphotype-specific electrical waveforms due to their morphological diversity. Received January 28, 2017; accepted April 24, 2017 Published online June 20, 2017